High SRD5A2 expression is associated with poor prognosis and promotes tumor cell progression in colorectal cancer - Jia, Meng-Fan; Dai, Meng-Nan; Hua, Kai-Ye; Du, Si-Yuan; Lu, Jian; Zhu, Ying-Wei (Translational Cancer Research, 2026)
Background: Steroid 5α-reductase type II (SRD5A2) is an enzyme that plays a significant role in steroid metabolism. It is mainly located in the endoplasmic reticulum membrane and can convert testosterone (T) into more active dihydrotestosterone (DHT). It plays a critical role in gender differentiation and androgen physiology, and is implicated in tumorigenesis and progression. It has been reported in various types of tumors. Among the most common gastrointestinal malignancies, colorectal cancer (CRC) imposes a significant global health burden. Nevertheless, the expression profile and clinical significance of SRD5A2 in CRC are poorly characterized, and its precise functional role requires further investigation. This study aimed to investigate the expression profile, prognostic significance, biological functions, and potential mechanisms of SRD5A2 in CRC.Methods: This retrospective cohort study included 180 patients with CRC. Tissue microarrays (TMAs) were constructed and subjected to SRD5A2 immunohistochemistry (IHC), and H-scores were used to stratify patients into high- and low-expression groups for clinicopathological and overall survival (OS) analyses. Univariate and multivariate Cox regression analyses, as well as subgroup Kaplan-Meier analyses, were performed to evaluate the prognostic value and stability of SRD5A2. In vitro, SRD5A2 knockdown was performed in CRC cells, followed by assays of cell viability, migration, invasion, and apoptosis. Epithelial-mesenchymal transition (EMT)-related proteins, classical oncogenic signaling pathways, and metabolic homeostasis were further evaluated by western blotting (WB), glucose consumption, adenosine triphosphate (ATP), and reactive oxygen species (ROS) assays.Results: SRD5A2 expression was significantly upregulated in CRC tissues compared with paired distal normal mucosa (P